2023
DOI: 10.3390/educsci13050514
|View full text |Cite
|
Sign up to set email alerts
|

Blended Learning in a Higher Education Context: Exploring University Students’ Learning Behavior

Abstract: Blended learning is a growing phenomenon in higher education after the COVID-19 pandemic (the educational process moved entirely online), and the way is prepared for blended education mode in universities. Although blended learning research is on the rise, fewer studies regard university students’ learning behavior in blended learning environments. This study aims to investigate university students’ blended learning behavior perceptions shortly after the pandemic. A 19-item questionnaire was administered to 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
(80 reference statements)
0
2
0
1
Order By: Relevance
“…Parallel insights from Xu and Zou (2023) reinforce this relationship, particularly highlighting its significance during the pandemic. Emphasizing a blended approach as a suitable mode of delivery for micro-credentials, we draw on the flexibility, convenience and self-learning opportunities it offers (Nikolopoulou and Zacharias, 2023). However, the study invites future research to validate the correlation between the blended approach and micro-credential effectiveness through experimental or longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Parallel insights from Xu and Zou (2023) reinforce this relationship, particularly highlighting its significance during the pandemic. Emphasizing a blended approach as a suitable mode of delivery for micro-credentials, we draw on the flexibility, convenience and self-learning opportunities it offers (Nikolopoulou and Zacharias, 2023). However, the study invites future research to validate the correlation between the blended approach and micro-credential effectiveness through experimental or longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Ini didukung oleh penelitian yang menunjukkan bahwa penerimaan niat positif dipengaruhi oleh persepsi siswa tentang pengaruh sosial, kondisi yang memfasilitasi, persepsi kegembiraan, manajemen belajar mandiri, dan efikasi diri. Namun, harapan kinerja dan harapan upaya tidak signifikan (Nikolopoulou & Zacharis, 2023). Aspek "Kecemasan" dalam konteks blended learning biasanya merujuk pada kekhawatiran atau rasa takut yang dialami oleh peserta didik atau pengajar saat menggunakan teknologi atau platform digital dalam proses belajar mengajar.…”
Section: Items Onunclassified
“…Immediately after the pandemic, Greek students expressed a preference for both in-person and blended approaches for learning, and their perceived blended learning benefits include adaptability for working students and SRL [34]. Another study [35] revealed students' positive blended learning behavior-perceptions with regard to online audio-visual resources that facilitate/support their independent learning. Postgraduate students also expressed strong beliefs for mobile technology's learning benefits and possibilities (flexibility in learning, collaboration among students, improvement of skills, etc.…”
Section: Introductionmentioning
confidence: 99%